On Paraphilias: Definition, Etiology, Forms, Clinical Treatment and Prognosis - Kron, Leposava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2009)
In this paper, the problems of paraphilias, definition, aetiology, clinical treatment and prognosis have been analysed. Psychologists and psychiatrists codified paraphilias as disorders (DSM-IV- R), as a replacement for the legal constructs of perversion or sodomy and describe them as recurrent, intense sexually arousing fantasies, sexual urges, or behaviours generally involving nonhuman objects, or the suffering or humiliation of a partner, children or other nonconsenting persons.